Nanosheet flower-cluster-shaped Ni-Fe-O-S / NF catalyst and preparation method thereof

The ZIF-67/NF derivatization strategy directly synthesized nano-flake cluster Ni-Fe-O-S/NF catalysts, which solved the problems of complex preparation process of existing dual-function electrocatalysts and high cost of precious metal catalysts, and achieved the optimization of efficient dual-function activity and full water-removing performance.

CN119869560AActive Publication Date: 2025-04-25ZHEJIANG UNIV

Patent Information

Application Number
CN202411956038.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-25
Estimated Expiration
2044-12-28

AI Technical Summary

Technical Problem

The preparation process of existing dual-function electrocatalysts is complicated, resulting in the inability to fully exert catalytic activity, and the reserves of precious metal catalysts are scarce and costly, which cannot meet the needs of large-scale industrial applications.

Method used

The nano-flake cluster Ni-Fe-O-S/NF catalyst was directly synthesized using the ZIF-67/NF derivatization strategy. Ni-Fe LDH was grown in situ on the conductive foam nickel substrate by etching ZIF-67, and then pyrolysis and vulcanization were performed to form a heterogeneous catalyst.

Benefits of technology

The efficient dual-function activity of the catalyst is achieved, the preparation cost and complexity are reduced, the problems of active site occlusion and poor conductivity are avoided, and the HER and OER activities and full water-removing properties are significantly optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869560A_ABST
    Figure CN119869560A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical engineering, and particularly relates to a nanosheet flower-cluster-shaped Ni-Fe-O-S / NF catalyst and a preparation method thereof. The invention relates to a nano-sheet flower-cluster-shaped Ni-Fe-O-S / NF electrode material prepared through a ZIF-67 / NF derivation strategy, namely, the Ni-Fe-O-S / NF electrode material disclosed by the invention is directly grown on a conductive foam nickel substrate in situ by etching ZIF-67; the high-activity difunctional electrocatalyst mainly relates to transition metals such as Ni, Fe, S and O. When the Ni-Fe-O-S / NF catalyst disclosed by the invention is applied to 1.0 M KOH electrolyzed water, the Ni-Fe-O-S / NF catalyst shows good bifunctional catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical industry, and particularly relates to a nano-sheet flower cluster Ni-Fe-OS / NF catalyst and a preparation method thereof. Background Art

[0002] The continuous use of traditional fossil energy has led to increasingly serious environmental pollution and energy shortage problems. Finding an environmentally friendly and sustainable energy source to gradually replace traditional fossil energy has become a focus of widespread attention. Hydrogen energy has high energy density, is environmentally friendly and renewable, and is considered to be one of the most ideal energy sources in the future. Among the many hydrogen production technologies, water electrolysis technology can quickly and pollution-freely obtain high-purity hydrogen, and is a green hydrogen production technology. However, the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) processes included in water electrolysis involve multiple electron transfer steps, which leads to an increase in the energy barrier of the entire reaction and a high overpotential. In order to accelerate the reaction process and reduce the overpotential, a catalyst is usually introduced. Precious metal-based materials (such as Pt-, Ru / Ir-, etc.) are a class of efficient electrochemical catalysts that are widely used in the field of water electrolysis hydrogen production technology. However, precious metal catalysts generally exhibit a single hydrogen or oxygen evolution activity, and their reserves are scarce and their geographical distribution is uneven, which cannot meet the needs of large-scale industrial applications. The development of bifunctional electrocatalysts can simplify the preparation process of electrode materials, reduce costs, and play a positive and important role in optimizing the structure of electrolyzers. Therefore, it is of great significance to develop low-cost and highly active bifunctional electrocatalytic materials.

[0003] In the study of non-precious metal electrocatalysts, nickel-based sulfide catalytic materials have attracted much attention due to their diverse chemical compositions and adjustable electronic environments. However, nickel-based sulfide catalysts generally show poor single HER or OER catalytic activity. Introducing other HER and OER catalytically active substances into nickel-based sulfides to form heterogeneous catalysts can activate active sites and thus enhance HER and OER activities, which is one of the most direct and effective ways to achieve dual-functional catalytic activity.

[0004] At present, most bifunctional electrocatalysts are built by step-by-step assembly. This method not only has a cumbersome preparation process, but also the materials introduced later may cover the active sites of the catalyst, resulting in a significant reduction in the final catalyst activity. For example, the patent with publication number CN113584521A discloses a branch-and-leaf heterostructure bifunctional electrocatalyst built by step-by-step assembly; first, NiMoO4 nanorods are synthesized on a nickel foam substrate, followed by phosphating to form NiMo-P nanorods, and then CoFe-LDH nanosheets are deposited on the NiMo-P nanorods by electrodeposition technology; a multi-component bifunctional electrocatalyst is formed in three steps. The obtained NiMo-P@CoFe-LDH electrocatalyst shows certain electrocatalytic activity and stability. However, the complex preparation process and step-by-step assembly process make it impossible for the catalyst to exert a more efficient catalytic activity to a certain extent.

[0005] Therefore, it is necessary to develop an overall construction strategy for the direct synthesis of heterogeneous catalytic materials with different HER and OER activities. 2 andFeNi 2 S 4 It has good HER catalytic activity. At the same time, NiS and NiO as OER active species have also received widespread attention. The patent with publication number CN 110918103 A discloses a three-phase NiS-NiS 2 -Ni 3 S 4 The electrocatalyst is characterized by an independent NiS-NiS formed by a three-phase nickel sulfide outer layer and a three-phase nickel sulfide inner layer. 2 -Ni 3 S 4 The nickel sulfide composite electrocatalyst constructed by the method exposes abundant active sites, improves interfacial electron transport, and promotes the hydrogen evolution reaction. 2 -Ni 3 S 4 The HER activity of the catalyst is still poor, and the researchers have not conducted further research on the oxygen evolution reaction.

[0006] Therefore, it is of great significance to develop an overall preparation strategy to directly generate nickel-based sulfide heterogeneous electrocatalysts with HER and OER activities through rational design, and to utilize the synergistic effect between different components and the improved electronic environment to achieve efficient bifunctional catalytic activity of the catalyst. Summary of the invention

[0007] The main technical problem solved by the present invention is to provide a nano-sheet flower cluster Ni-Fe-OS / NF catalyst and a preparation method thereof.

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a nanosheet flower cluster Ni-Fe-OS / NF catalyst, comprising the following steps:

[0009] 1) Clean and dry the nickel foam (NF) (conventional cleaning and drying) to obtain clean NF;

[0010] 2) Dissolve the surfactant in deionized water to obtain solution A (surfactant solution).

[0011] The organic ligand is dissolved in liquid alcohol to obtain solution B (organic ligand solution 1).

[0012] Dissolving a cobalt source in liquid alcohol to obtain solution C (cobalt source solution);

[0013] The clean NF obtained in step 1) is first placed in solution A (surfactant solution) for ultrasonic activation to obtain surface activated NF;

[0014] After the surface activation, NF was placed in solution B (organic ligand solution 1), and then solution C (cobalt source solution) was immediately added and stirred evenly (stirring time was 0.5-1.5h), and then allowed to stand and grow for 11-13h at room temperature, and then washed and dried (baked) to obtain ZIF-67 / NF precursor;

[0015] The weight ratio of the organic ligand in the solution B to the cobalt source in the solution C is 3.2-3.4:1.4-1.5;

[0016] 3) dissolving the organic ligand in liquid alcohol to obtain solution D (organic ligand solution 2);

[0017] Dissolve the nickel source and the iron source in deionized water to obtain solution E (nickel source / iron source mixed solution); the molar ratio of the nickel source to the iron source is 2.5:1.4-1.6;

[0018] Solution D and solution E are mixed and stirred, and then the ZIF-67 / NF precursor obtained in step 2) is added, and then they are transferred into a high-pressure reactor and allowed to stand for 40 to 80 minutes, and then reacted at 120±10°C for 6±1h. After the reaction is completed, the mixture is washed to obtain Ni-FeLDH / NF (nano-flaky Ni-Fe hydroxide);

[0019] When the nickel source in solution E is 2.5 mmol, the organic ligand in solution D is 1.6-1.7 g;

[0020] 4) Pyrolyzing the Ni-Fe LDH / NF obtained in step 3) at 600-900° C. for 2±0.5 h under inert gas protection, and naturally cooling to room temperature to obtain Ni-Fe-O / NF;

[0021] 5) Under the protection of inert gas, sulfur powder is used as a sulfur source (the amount of sulfur powder is 0.1-0.3 g), and the Ni-Fe-O / NF obtained in step 4) is subjected to gas sulfurization heat treatment;

[0022] The heat treatment temperature is 150-350° C., and the heat treatment time is 0.5-1.5 h (preferably 300° C., 1 h) to obtain a nanosheet flower cluster Ni-Fe-OS / NF catalyst (multiphase Ni-Fe-OS / NF target sample).

[0023] As an improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0024] The surfactant is sodium polystyrene sulfonate;

[0025] The organic ligand is methylimidazole or dimethylimidazole;

[0026] The cobalt source is cobalt nitrate;

[0027] The nickel source is nickel nitrate;

[0028] The iron source is ferric nitrate;

[0029] The sulfur source is sulfur powder.

[0030] As a further improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0031] The liquid alcohol is methanol;

[0032] The inert gas is argon.

[0033] As a further improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0034] The ultrasonic activation time in step 2) is 50 to 70 minutes.

[0035] As a further improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0036] Step 4) The heating rate is 9-11°C / min,

[0037] Step 5) The heating rate is 4-6°C / min.

[0038] As a further improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0039] The inert protective gas is argon.

[0040] As a further improvement of the preparation method of the nanosheet flower cluster Ni-Fe-OS / NF catalyst of the present invention:

[0041] Dissolve 40 mg of sodium polystyrene sulfonate in 50 ± 5 mL of deionized water to obtain solution A (surfactant solution);

[0042] Dissolve 3.28 g of dimethylimidazole / methylimidazole in 50 ± 5 mL of methanol to obtain solution B (organic ligand solution 1);

[0043] Dissolve 1.45 g of cobalt nitrate hexahydrate in 50 ± 5 mL of methanol to obtain solution C (cobalt source solution);

[0044] Dissolve 1.64 g of dimethylimidazole in 10 ± 1 mL of methanol to obtain solution D (organic ligand solution 2);

[0045] Dissolve 2.5 mmol nickel nitrate hexahydrate and 1.5 mmol iron nitrate hexahydrate in 20±2 mL deionized water to obtain solution E (nickel source / iron source mixed solution);

[0046] 0.2 g sulfur powder was used as the sulfur source.

[0047] Note: NF cut to 2×3cm 2 size.

[0048] The present invention also provides a nanosheet flower cluster Ni-Fe-OS / NF catalyst prepared by any of the above methods.

[0049] The present invention is a nano-sheet flower cluster Ni-Fe-OS / NF electrode material prepared by a ZIF-67 / NF derivatization strategy, wherein the highly active bifunctional electrocatalyst mainly involves transition metals Ni, Fe, S, and O. The Ni-Fe-OS / NF of the present invention is directly grown in situ on a conductive nickel foam substrate by etching ZIF-67.

[0050] The nanosheet flower cluster Ni-Fe-OS / NF catalyst (for efficient full water splitting multiphase nanosheet Ni-Fe-OS / NF catalyst) of the present invention mainly overcomes the problems of single catalytic activity, few active sites and poor stability of the catalyst in the prior art, and more importantly, avoids the covering of active sites and the resulting poor conductivity caused by the coating step, and also solves the deficiency of damage to the active sites caused by the step-by-step synthesis during the conventional preparation of bifunctional catalysts. The preparation method of the present invention is ingenious, simple and effective in promoting the in-situ growth of multiphase catalysts on a conductive substrate (nickel foam), thereby enhancing the conductivity of the catalyst; at the same time, a multiphase electrocatalytic material with both HER and OER activity is directly generated, generating a synergistic effect and effectively activating the catalyst active sites. In addition, the in-situ growth multiphase Ni-Fe-OS / NF catalyst of the present invention couples the multiphase to produce a synergistic effect while regulating the electronic configuration, accelerating electron transfer, and enhancing the conductivity. The Ni-Fe-OS / NF catalyst shows excellent HER and OER activity and full water splitting performance, providing a valuable reference for the preparation of efficient bifunctional electrocatalysts.

[0051] The Ni-Fe-OS / NF catalyst with optimized electronic configuration has excellent electrochemical activity in alkaline electrolyte. -2 At a current density of 1.5 Hz, the HER overpotential is only 92 mV, and the OER overpotential is as low as 90 mV. In addition, only 1.49 V full water splitting cell voltage is required to achieve 10 mA cm -2 The current density is higher than 100000 and the stable operation time is more than 150h, which significantly optimizes the existing Pt / C-IrO 2 Precious metal electrocatalysts. The excellent electrocatalytic activity of Ni-Fe-OS / NF catalyst for water splitting provides a simple and effective synthetic strategy for the preparation of dual-functional electrocatalysts.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The present invention adopts the ZIF-67 / NF etching derivatization strategy to directly generate a Ni-Fe-OS / NF catalyst with multi-phase components and unique nanosheet flower cluster structure. The designed ZIF-67 / NF etching derivatization strategy provides a favorable structural advantage that makes it easier for the catalytic material to grow in situ on the NF, and the etching and regrowth process effectively regulates the electronic environment of the catalyst and improves the catalytic activity. In addition, the introduction of Ni and Fe sources in the solvothermal process affects the oxidation process of nickel, which promotes the formation of multi-phase catalysts after the subsequent sulfurization step. Subsequently, the high-temperature pyrolysis of the hydroxide causes the decomposition of the hydroxyl group to form a large amount of water vapor, resulting in a porous structure of the nanosheet. Reasonable pyrolysis regulation obtains a beneficial porous nanosheet structure, enhances the diffusion of the electrolyte, and increases the contact between the catalyst and the electrolyte. In the last step of high-temperature sulfurization treatment, by screening and precise control of the sulfurization conditions, not only the porous morphology structure of the Ni-Fe-OS / NF catalyst is retained, but also NiS is directly generated. 2 ,NiS,FeNi 2 S 4 and NiO multiphase components ( Figure 1 ). The favorable multiphase components and morphological structures formed by the Ni-Fe-OS / NF catalyst lead to the exposure of abundant active sites and large electrochemical active areas. The overall synthesis strategy of the multiphase Ni-Fe-OS / NF catalyst designed in the present invention is simple and effective, and is suitable for directly generating multiphase catalysts. By adopting the ZIF-67 / NF derivatization strategy, controlling the relative addition amount of the nickel-iron source, the pyrolysis temperature, the sulfurization conditions and other parameters, the generation of multiphase nanosheet flower cluster Ni-Fe-OS / NF catalysts with high bifunctional catalytic activity was successfully achieved.

[0054] (2) The Ni-Fe-OS / NF catalyst of the present invention exhibits good bifunctional catalytic activity when applied to 1.0 M KOH water electrolysis. The Ni-Fe-OS / NF catalyst can reach 10 mA cm with only 90 and 92 mV OER and HER overpotentials. -2 , the Taffeta slopes are 43 and 95 mV dec respectively. -1 The catalyst can be operated stably for more than 150 hours without any detachment or obvious morphological deformation. When the Ni-Fe-OS / NF catalyst was used for the full water splitting test, a low full water splitting cell voltage of 1.49 V was shown at 10 mA cm -2 Under the same current density, the stable performance can also run for 150h to maintain a linear voltage curve without obvious catalyst shedding. The overall performance is significantly better than that of precious metal-based PtC and IrO 2 Electrocatalyst.

[0055] In summary, the present invention uses Ni and Fe to etch ZIF-67 / NF to grow Ni-Fe LDH / NF, then pyrolyzes it in an argon atmosphere to obtain Ni-Fe-O / NF, and finally directly synthesizes a multiphase Ni-Fe-OS / NF catalyst through inert gas sulfurization treatment. The characteristics of the present invention are that the catalyst preparation process is simple and the raw materials are readily available. More importantly, it can directly synthesize multiphase electrocatalysts and achieve a specific porous nanosheet flower cluster structure. In addition, the electronic environment of the catalyst is favorably regulated. In 1.0M KOH electrolyte, the Ni-Fe-OS / NF catalyst shows excellent HER and OER catalytic activity and complete water splitting catalytic performance. This provides useful inspiration for the development of direct synthesis of multiphase high-activity bifunctional electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.

[0057] Figure 1 The XRD pattern of the Ni-Fe-OS / NF catalyst prepared in Example 1 of the present invention (including the products obtained in each step);

[0058] according to Figure 1 It can be seen that the prepared Ni-Fe-OS / NF catalyst shows a multiphase composition, including NiS (PDF#86-2281), NiS 2 (PDF#73-0574),FeNi 2 S 4 (PDF#47-1740) and NiO (PDF#47-1049).

[0059] Figure 2 The OER: LSV diagram of the Ni-Fe-OS / NF catalyst prepared in Example 1 of the present invention (including the products obtained in each step);

[0060] according to Figure 2 It can be seen that the prepared heterogeneous Ni-Fe-OS / NF catalyst shows excellent OER performance. It is worth noting that the OER performance of the heterogeneous Ni-Fe-OS / NF catalyst prepared in the present invention is significantly better than that of the precious metal IrO 2 catalyst.

[0061] Figure 3 HER:LSV diagram of the Ni-Fe-OS / NF catalyst prepared in Example 1 of the present invention (including the products obtained in each step);

[0062] according to Figure 3 It can be seen that the prepared multiphase Ni-Fe-OS / NF catalyst shows competitive HER catalytic activity.

[0063] Figure 4 This is the complete water decomposition diagram of the Ni-Fe-OS / NF catalyst (including the products obtained in each step) prepared in Example 1 of the present invention;

[0064] according to Figure 4 It can be seen that the prepared heterogeneous Ni-Fe-OS / NF catalyst shows excellent overall water splitting performance at 10 mA cm -2 At the current density, the voltage of the full water splitting cell is as low as 1.49V. In addition, the prepared multiphase Ni-Fe-OS / NF catalyst has a full water splitting performance far exceeding that of PtC||IrO 2 Precious metal catalysts. DETAILED DESCRIPTION

[0065] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0066] The speed of vigorous stirring is 1200±200 rpm.

[0067] Example 1

[0068] (1) Cut nickel foam (NF) into 2×3 cm 2 The size was firstly ultrasonically cleaned in 3.0 M hydrochloric acid for 60 min, then ultrasonically cleaned in ethanol and deionized water for 30 min respectively, and then dried in a vacuum drying oven at 70 °C overnight (about 12 h) to obtain clean NF.

[0069] (2) Under conventional stirring conditions: 40 mg of sodium polystyrene sulfonate was dissolved in 50 mL of deionized water to obtain a surfactant solution (solution A); 3.28 g of dimethylimidazole was dissolved in 50 mL of methanol to obtain an organic ligand solution (solution B); 1.45 g of cobalt nitrate hexahydrate was dissolved in 50 mL of methanol to obtain a cobalt source solution (solution C);

[0070] The clean NF obtained in step (1) is first placed in solution A to perform ultrasonic surface activation for 1 hour to obtain surface activated NF;

[0071] After the surface activated NF was placed in solution B, solution C was immediately added and vigorously stirred for 30 minutes. After that, it was allowed to grow at room temperature for 12 hours. After that, it was washed (rinsed three times with methanol and deionized water respectively) and dried in a vacuum oven at 70°C overnight to obtain the ZIF-67 / NF precursor.

[0072] (3) Under conventional stirring conditions: dissolving 1.64 g of dimethylimidazole in 10 mL of methanol to obtain an organic ligand solution II (solution D); dissolving 2.5 mmol of nickel nitrate hexahydrate and 1.5 mmol of ferric nitrate hexahydrate in 20 mL of deionized water to obtain a nickel source / iron source mixed solution (solution E);

[0073] After solution D and solution E are fully mixed and stirred, the ZIF-67 / NF precursor obtained in step (2) is added, and then transferred into a high-pressure reactor and allowed to stand for 60 minutes, and then reacted at 120°C for 6 hours. After the reaction is completed, the mixture is cleaned (rinsed three times with methanol and deionized water respectively), and then dried in a vacuum drying oven at 70°C overnight to obtain nano-sheet Ni-Fe hydroxide (Ni-FeLDH / NF).

[0074] (4) heating the Ni-Fe LDH / NF obtained in step (3) to 600° C. for pyrolysis under Ar gas for 2 h, and then naturally cooling to room temperature to obtain Ni-Fe-O / NF;

[0075] The heating rate is 10°C / min.

[0076] (5) Under the protection of Ar gas, using sulfur powder as a sulfur source, the Ni-Fe-O / NF obtained in step (4) is subjected to a separate gas sulfurization reaction;

[0077] That is, the Ni-Fe-O / NF obtained in step (4) is heated to 300°C together with 0.2 g of sulfur powder at a heating rate of 5°C / min, and then heat-treated at 300°C for 1 hour to directly obtain a multiphase Ni-Fe-OS / NF electrocatalyst (nanosheet flower cluster Ni-Fe-OS / NF catalyst).

[0078] Experiment 1: According to conventional detection methods, the heterogeneous Ni-Fe-OS / NF electrocatalyst prepared in Example 1 can reach 10 mA cm-2 with only 90 and 92 mV OER and HER overpotentials in 1.0 M KOH. -2 The current density is 10 mA cm -2 , the voltage of the fully water-dissolving electrolytic cell is as low as 1.49V.

[0079] The ZIF-67 / NF precursor obtained in step (2) of Example 1, the Ni-Fe LDH / NF obtained in step (3), and the Ni-Fe-O / NF obtained in step (4) were tested according to the method of Experiment 1, and the obtained properties are described in Table 1 below.

[0080] Table 1

[0081]

[0082] Comparative Example 1 Series

[0083] Compared with Example 1, the amount of nickel nitrate hexahydrate and ferric nitrate hexahydrate in step (3) of "2.5mmol nickel nitrate hexahydrate, 1.5mmol ferric nitrate hexahydrate dissolved in 20mL deionized water" is changed to the amount shown in Table 2 below; the rest is the same as Example 1, thereby obtaining the corresponding Comparative Examples 1-1 to Comparative Examples 1 to 5. The test was carried out according to the method of Experiment 1, and the obtained properties are shown in Table 2 below.

[0084] Table 2

[0085]

[0086] Comparative Example 2 Series

[0087] Relative to Example 1, step (4) "600°C pyrolysis for 2h" was changed to the pyrolysis temperature and pyrolysis time as described in Table 3 below, and the rest was the same as Example 1, thereby obtaining corresponding Comparative Examples 2-1 to Comparative Examples 2-3. The test was carried out according to the method of Experiment 1, and the obtained properties were as described in Table 3 below.

[0088] Table 3

[0089]

[0090] Comparative Example 3 Series

[0091] Relative to Example 1, the "0.2 g sulfur powder" in step (5) was changed to the amount of sulfur powder as described in Table 4 below, and the rest was the same as Example 1, thereby obtaining corresponding Comparative Examples 3-1 to Comparative Examples 3 to 5. The test was carried out according to the method of Experiment 1, and the obtained properties were described in Table 4 below.

[0092] Table 4

[0093]

[0094] Comparative Example 4 Series

[0095] Relative to Example 1, the "300°C heat treatment for 1 h" in step (5) was changed to the heat treatment temperature and heat treatment time as described in Table 5 below, and the rest was the same as Example 1, thereby obtaining corresponding Comparative Examples 4-1 to Comparative Examples 4-4. The test was carried out according to the method of Experiment 1, and the obtained properties were described in Table 5 below.

[0096] Table 5

[0097]

[0098]

[0099] Comparative Example 5: Step (2) of Example 1 is omitted, that is, the preparation of ZIF-67 / NF precursor is omitted, and the ZIF-67 / NF precursor in step 3) is replaced with clean NF, and the rest is the same as Example 1. The electrocatalyst obtained is tested according to the method described in Experiment 1. -2 The overpotentials of 147 mV OER and 167 mV HER were shown at the current density.

[0100] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a nanosheet flower cluster Ni-Fe-OS / NF catalyst, characterized in that: Nanosheet flower cluster Ni-Fe-OS / NF catalyst was prepared by ZIF-67 / NF derivatization strategy.

2. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 1, characterized in that: The following steps are involved: 1) Clean and dry the nickel foam to obtain clean NF; 2) Dissolve the surfactant in deionized water to obtain solution A. The organic ligand is dissolved in liquid alcohol to obtain solution B. Dissolving a cobalt source in liquid alcohol to obtain solution C; The clean NF obtained in step 1) is first placed in solution A for ultrasonic activation to obtain surface activated NF; After the surface activated NF was placed in solution B, solution C was immediately added and stirred evenly, and then allowed to grow at room temperature for 11 to 13 hours, and then washed and dried to obtain the ZIF-67 / NF precursor; The weight ratio of the organic ligand in the solution B to the cobalt source in the solution C is 3.2-3.4:1.4-1.5; 3) dissolving the organic ligand in liquid alcohol to obtain solution D; Dissolve the nickel source and the iron source in deionized water to obtain solution E; the molar ratio of the nickel source to the iron source is 2.5:1.4-1.6; Solution D and solution E are mixed and stirred, and then the ZIF-67 / NF precursor obtained in step 2) is added, and then transferred into a high-pressure reactor, first allowed to stand for 40 to 80 minutes, and then reacted at 120±10°C for 6±1h. After the reaction is completed, the mixture is cleaned to obtain Ni-Fe LDH / NF; When the nickel source in solution E is 2.5 mmol, the organic ligand in solution D is 1.6-1.7 g; 4) Pyrolyzing the Ni-Fe LDH / NF obtained in step 3) at 600-900° C. for 2±0.5 h under inert gas protection, and naturally cooling to room temperature to obtain Ni-Fe-O / NF; 5) Under the protection of inert gas, using sulfur powder as a sulfur source, the Ni-Fe-O / NF obtained in step 4) is subjected to gas sulfurization heat treatment; The heat treatment temperature is 150-350° C., and the heat treatment time is 0.5-1.5 h, to obtain a nanosheet flower cluster Ni-Fe-OS / NF catalyst.

3. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 2, characterized in that: The surfactant is sodium polystyrene sulfonate; The organic ligand is methylimidazole or dimethylimidazole; The cobalt source is cobalt nitrate; The nickel source is nickel nitrate; The iron source is ferric nitrate; The sulfur source is sulfur powder.

4. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 3, characterized in that: The liquid alcohol is methanol; The inert gas is argon.

5. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 4, characterized in that: The ultrasonic activation time in step 2) is 50 to 70 minutes.

6. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 5, characterized in that: Step 4) The heating rate is 9-11°C / min, Step 5) The heating rate is 4-6°C / min.

7. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to claim 6, characterized in that: The inert protective gas is argon.

8. The method for preparing the nanosheet flower cluster Ni-Fe-OS / NF catalyst according to any one of claims 1 to 7, characterized in that: Dissolve 40±4 mg of sodium polystyrene sulfonate in 50±5 mL of deionized water to obtain solution A; Dissolve 3.28±0.3 g of dimethylimidazole / methylimidazole in 50±5 mL of methanol to obtain solution B; Dissolve 1.45±0.1 g of cobalt nitrate hexahydrate in 50±5 mL of methanol to obtain solution C; Dissolve 1.64±0.1 g of dimethylimidazole in 10±1 mL of methanol to obtain solution D; Dissolve 2.5 mmol nickel nitrate hexahydrate and 1.5 mmol iron nitrate hexahydrate in 20 ± 2 mL deionized water to obtain solution E; 0.2 g sulfur powder was used as the sulfur source.

9. The nanosheet flower cluster Ni-Fe-OS / NF catalyst prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite electrocatalyst and preparation method and application thereof

    CN110918103A

  • Branch and leaf type heterostructure complete water splitting catalyst and preparation method thereof

    CN113584521A

  • Hollow core-shell structure supercapacitor material Fe-Co-S / NF as well as preparation method and application thereof

    CN110176360A

  • Electrocatalyst based on FeOOH-NiOOH / NF and preparation method of electrocatalyst

    CN110479281A

  • Synthetic method for simultaneously preparing positive electrode material and negative electrode material of high-performance supercapacitor by taking Co-MOF array as precursor

    CN114664572A

Cited By

  • Transition metal catalyst and preparation method and application thereof

    CN121381063A